2000
DOI: 10.2105/ajph.90.10.1595
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and screening practices among older men regarding prostate cancer

Abstract: OBJECTIVES: This study determined population-based rates of reported prostate cancer screening and assessed prostate cancer-related knowledge, attitudes, and screening practices among men in New York aged 50 years and older. METHODS: Two telephone surveys were conducted. One was included in the 1994 and 1995 statewide Behavioral Risk Factor Surveillance System interviews, and the other was a community-level survey that targeted Black men (African-American Men Survey). Prevalence estimates were computed for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(36 citation statements)
references
References 32 publications
7
29
0
Order By: Relevance
“…We also report that persons with lower perceived barriers have higher rates of cancer screening. This finding is consistent with previous studies reporting fear of cancer, fear of pain, and embarrassment to be significant predictors of lower screening rates for breast, prostate, colorectal, and cervical cancer (3543). …”
Section: Discussionsupporting
confidence: 93%
“…We also report that persons with lower perceived barriers have higher rates of cancer screening. This finding is consistent with previous studies reporting fear of cancer, fear of pain, and embarrassment to be significant predictors of lower screening rates for breast, prostate, colorectal, and cervical cancer (3543). …”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were reported in a study among older men in New York, where as many as 18% thought that they were at no risk of acquiring prostate cancer while 31% did not know whether they were at risk of acquiring prostate cancer [14]. …”
Section: Discussionsupporting
confidence: 86%
“…Similarly, our study results revealed that only 12.3% of the respondents had ever been advised by a health worker to undergo prostate cancer screening. Studies have attributed the lack of participation in prostate cancer prevention activities to economic limitations, lack of awareness, low level of education, fear, cultural and religious beliefs, and traditional attitudes about male gender and physician’s attitudes [14,16]. In addition, some researchers have identified sexual dysfunction as a sensitive issue for black men, which discourages their involvement in prostate cancer screening [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, goals innovative measure must be applied to overcome the perceived barriers that hinders early screening practices for prostate cancer, create mechanisms to partake support and reinforce men to healthy choice (healthy people, 2010). Screening is a very big issue especially in black men as compare to women (Woods et al, 2004 facilities, lack of knowledge about studies, past negative experience, physician attitude, cultural and religious believes/attitude and various erection negative factors preventing an individual participation in prostate cancer examination (Steele et al, 2000); and only 46.5% of their study participants indicated that they have heard about prostate cancer screening and 68.8% indicated interest for screening.…”
Section: Sign and Symptoms Of Prostate Cancermentioning
confidence: 99%